2019
DOI: 10.24136/oc.2019.012
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of the protection against misleading commercial practices: ongoing divergences in Central European countries

Abstract: Research background: Modern European integration focuses on competition in the internal single market, embracing both competitiveness and consumer protection, and it aims at full harmonization in this arena. The hallmark, the Unfair Commercial Practices Directive from 2005, aims to overcome diverse social, political, legal and economic traditions. Is the implied protection against misleading practices an opportunity or a threat for Central European Regions? Purpose of the article: The primary purpose is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Consequently, the EU has newly set a legal duty for large public-interest entities with more than 500 employees to include, in the management report, a non-financial statement linked to CSR [46], see Directive 2013/34/EU, Directive (EU) 2017/1132 and Regulation 2015/884 as updated [15]. The EU motto "united in diversity" neatly fits in with the perception of CSR as a dialogue and interaction between businesses, corporations, and their stakeholders [47] including customers [43] and is reflected by EU policies [48,49], which, so far, lead to only one legal duty regarding CSR for only some subjects-to report about it. Thusly, so far, it is up to the discretion of the businesses how much they will engage with CSR and its six categories, how they use it as competition leverage [44], and inform about it [10].…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…Consequently, the EU has newly set a legal duty for large public-interest entities with more than 500 employees to include, in the management report, a non-financial statement linked to CSR [46], see Directive 2013/34/EU, Directive (EU) 2017/1132 and Regulation 2015/884 as updated [15]. The EU motto "united in diversity" neatly fits in with the perception of CSR as a dialogue and interaction between businesses, corporations, and their stakeholders [47] including customers [43] and is reflected by EU policies [48,49], which, so far, lead to only one legal duty regarding CSR for only some subjects-to report about it. Thusly, so far, it is up to the discretion of the businesses how much they will engage with CSR and its six categories, how they use it as competition leverage [44], and inform about it [10].…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…Both the concept of sustainability and CSR are outcomes of the belief that businesses, especially large global companies, as powerful economic, social and political actors, should participate in the multi-stakeholder model and be pro-sustainability [40,41]. CSR means the responsibility towards all stakeholders, that is, towards the entire society, while addressing all three sustainability pillars [38] and even fair competition [42][43][44]. Responsibility, as such, has Latin roots, see respondere, and means that someone has to answer for the effects caused by him to an authority and this authority evaluates its damages [1].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…For the EU and EU member states, sustainability in the large sense represents a current multi-stakeholder relationship of virtually all members of society and even the society itself. Although the resulting CSR is only partially covered by mandatory EU law provisions and national law provisions (MacGregor Pelikánová, 2019b), the CSR that came of this represents a transparent dialogue and interaction between businesses and other stakeholders which should be materialized, among others, by publicly available financial reporting and non-financial reporting, i.e. CSR reporting (MacGregor Pelikánová, R. & MacGregor, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They have been confronted with positive as well as negative influences (MacGregor Pelikánová, 2019a;Petera et al, 2019). Indeed, a myriad of meta-analytic, horizontal and vertical studies have shown (i) that human's concern for others has rather decreased during the last decades (Konrath, 2011;MacGregor Pelikánová, 2019b) and (ii) that more altruism and sustainability awareness and commitment is exhibited by responsible people, i.e. the positive attitude towards CSR often co-relates with the positive attitude to the responsibility duty (Peterson, 1983).…”
Section: Literature Reviewmentioning
confidence: 99%